Keselamatan Dan Keamanan Pelayaran Di Laut Indonesia Berdasarkan UNCLOS 1982 - Gincya Azifqi Giardinni; Irda Tri Fauziah; Dewi Rahmawati Gustini (Peneliti.net, 2023)
Geographically, most of the earth is made up of oceans. So the sea has a very important role in the life of mankind. Water activities place the sea into a vital role in human life, especially for the people of Indonesia whose territory is 70% ocean. Security and safety at sea need more attention, to minimize the existence of non-traditional threats, such as separatism and maritime terrorism piracy. With law enforcement at sea, security, and safety means that the sea can be controlled safely for water activities. The enforcement of the sea is an integral part of the world's territory that results in a clash of interests, thus the utilization and use of the sea must be regulated by laws that have been agreed upon nationally and internationally, such as the 1982 UNCLOS Conference which includes matters regarding the codification of existing provisions of the law of the sea, the development of existing laws of the sea, and the creation of new rules. However, the marine transportation safety and security system in Indonesia has not run optimally as planned, there are still many accidents due to both natural and human factors. Government policies in the maritime sector, both the fishing industry and the shipping industry have not been implemented consistently by applicable laws. So far, the development of maritime potential has been hampered by structural problems and the absence of national political awareness and implementation of the legal basis that regulates the magnitude of economic, fisheries, and maritime potential.